2015
DOI: 10.1039/c4gc01354a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the hydroconversion of cinnamaldehyde using mechanochemically-synthesized Pd/Al-SBA-15 catalysts

Abstract: The hydroconversion of cinnamaldehyde was studied using a simple and efficient hydrogen-donating protocol catalyzed by mechanochemically synthesized bifunctional Pd/Al-SBA-15 catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Yepez et al. previously reported TEM images of pure Al‐SBA‐15 . In comparison, TEM images (Figure ) of representative catalysts synthesized in the present study show that the ordered porous structure of the Al‐SBA‐15 support was preserved upon Fe incorporation in continuous flow.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…Yepez et al. previously reported TEM images of pure Al‐SBA‐15 . In comparison, TEM images (Figure ) of representative catalysts synthesized in the present study show that the ordered porous structure of the Al‐SBA‐15 support was preserved upon Fe incorporation in continuous flow.…”
Section: Resultssupporting
confidence: 49%
“…Yepez et al previously reported TEM images of pure Al-SBA-15. [30] In comparison, TEM images ( The synthesized MNPs were employed as heterogeneous catalysts in the selective oxidative disruption of isoeugenol in the liquid phase by using aqueous hydrogen peroxide as a green oxidant, both at room temperature and at 90 8C( conventional heating). Figure 3d epictst he conversion of isoeuge- ucts.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, a progressive weight loss of 8.6% was observed from 100 °C to 800 °C. Around 200 °C, DTA analysis ( Figure 2, green line) displayed a slight endothermic band, related to unbounded/physisorbed solvents [26]. In addition DTA experiments showed two exothermic peaks at 340 °C and 420 °C, associated with the decomposition of sulfathiazole and 3chloro-propylmethoxysilane, respectively.…”
Section: Methodsmentioning
confidence: 96%
“…On the other side, Pd-based catalysts suffer from aggregation and deactivation in each run [17][18][19]. Necessity of Pd species engagement with a suitable ligand or support is inevitable in order to obtain an efficient, recyclable, and atom efficient catalyst [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%